The Truth Is Always Grey : A History of Modernist Painting - Guerin, Frances (Book collections on Project MUSE., 2018)
"Frances Guerin argues that painters select grey to respond to a key question of modernist art: What is painting? Presenting an impressive range of canonical paintings across centuries, this book is a treatise on color that allows us to see something entirely new in familiar paintings and encourages our appreciation for the innovation and dynamism of the color grey"--